The Effect of Morinda citrifolia and Arthrospira plattensis Powder on the Performance and Quality of Broiler Duck Carcasses - David Kurniawan; Citra Dewi Yulia Chistie (Jurnal Ilmu Ternak dan Veteriner, 2020)
This study was aimed to investigate performance and quality of broiler duck carcasses fed with Morinda citrifolia and Arthrospira plattensis. A total of 168 two-week-old broiler duck with an initial average body weight of 463 ± 29.38 g and a diversity of 6.35 % were randomly allotted to 7 experimental groups with 4 replications each with 6 bird per replication. Treatments were T0 (basal diet as a control), T1 (basal diet + 0.2% of Morinda citrifolia powder (MP)), T2 (basal diet + 0.5% of Arthrospira plattensis powde(AP)) , T3 (basal diet + 0.2% of MP+ 0.5% of AP), T4 (basal diet + 0.4% of MP + 0.5% of AP), T5 (basal diet + 0.2% of MP + 0.1% of AP), T6 (basal diet 0.4% of MP + 0.1% of AP). Variables measured were feed intake, body weight gain, feed conversion ratio, carcass percentage, abdominal fat, and visceral organ. Data were analyzed for variance based on a Completely Randomize Design and continued with Duncan’s multiple Range Test for differences. Result showed that the treatments did not affect (P>0.05) on feed intake, body weight gain and feed conversion ratio. The treatments also did not affect (P>0.05) carcass percentage, abdominal fat, and visceral organ. The diet did not significantly improve performance and quality of broiler duck carcasses.